2017
DOI: 10.1007/s00468-017-1524-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate–growth relationships of Schrenk spruce (Picea schrenkiana) along an altitudinal gradient in the western Tianshan mountains, northwest China

Abstract: The elevation-dependent tree growth patterns and climate-growth relationships were inferred from five tree-ring chronologies of Picea schrenkiana along an altitudinal gradient in the western Tianshan Mountains, northwest China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 43 publications
4
10
1
Order By: Relevance
“…Moisture stress is regarded as one of the main climatic stresses involved in the process of tree‐ring formation. The stress has been confirmed in dendroclimatological studies using Schrenk spruce tree‐ring samples for other regions in central Asia (Chen et al ., ; Huo et al ., ; Zhang et al ., ). Our correlation analyses indicated that the positive relationship between the radial growth of spruces and precipitation is strong, while the correlation between the regional tree‐ring width chronology and temperature is relatively low.…”
Section: Discussionmentioning
confidence: 98%
“…Moisture stress is regarded as one of the main climatic stresses involved in the process of tree‐ring formation. The stress has been confirmed in dendroclimatological studies using Schrenk spruce tree‐ring samples for other regions in central Asia (Chen et al ., ; Huo et al ., ; Zhang et al ., ). Our correlation analyses indicated that the positive relationship between the radial growth of spruces and precipitation is strong, while the correlation between the regional tree‐ring width chronology and temperature is relatively low.…”
Section: Discussionmentioning
confidence: 98%
“…In S2700 and S2900, tree growth was positively correlated (p < 0.05) with SPEI and precipitation, and more than 25% of BAI variation was explained by SPEI ( Figure 6c,e and Figure S3). This suggests water deficit inhibits tree growth and might weaken the benefit of climate warming especially in lower elevations, as also found in the Mediterranean regions, Central European, and southern Tibetan Plantae [14,16,33]. Higher MS values at low altitudes (Table 2) also suggest the water limit, as the mean sensitivity of tree rings are usually higher in arid sites than in wet sites [26].…”
Section: Discussionmentioning
confidence: 74%
“…Blooming was observed in the forests of the Xinjiang Tien Shan between in mid-May and July depending on the weather (Pan et al, 2013). Its lower altitudinal belt limit is responsive to moisture availability and its upper limit to temperature (Huo et al, 2017). It grows preferably on north-facing shady mountain slopes (Wu et al, 2015).…”
Section: Interpretation and Discussionmentioning
confidence: 99%